Effect of Diammonium Glycyrrhizinate in Improving Focal Cerebral Ischemia-Reperfusion Injury in Rats Through Multiple Mechanisms - Hong Wang; Binbin Zhang; Weiwei Dong; Yuying Li; Liwen Zhao; Ying Zhang (SAGE Publishing, 2022)
Objective Acute ischemic stroke is a current major disabling and killer disease worldwide. We aimed to investigate the protective effect and mechanism of diammonium glycyrrhizinate in alleviating acute ischemic stroke. Methods Ninety male Sprague Dawley (SD) rats (weighing 250-300 g) were randomly allocated into three groups: sham operation group (sham group), diammonium glycyrrhizinate group (DG group) and model group (model group) each with 30 individuals. A rat model of focal CIR injury was established by reversible middle cerebral artery occlusion. Results Zea-Longa scores for the rats in the DG group and model group were 7-fold and 8-fold higher than those of the sham group 2 h post-surgery (2.90 ± 0.99 vs. 0.30 ± 0.53, P < .05; 2.80 ± 0.61 vs. 0.30 ± 0.53, P < .05, respectively). Three days after model establishment, the scores of DG group were 26.92% lower compared with those of the model group (1.90 ± 0.76 vs. 2.60 ± 0.62, P < .05). In addition, compared with the sham group, the number of Nissl bodies and Akt-positive cells in were 27.35% and 30.42% lower in the hippocampus of the DG group (Nissl bodies: 83.40 ± 7.01 vs. 115.60 ± 11.97, p < 0.05; Akt-positive cells: 94.70 ± 8.23 vs. 136.10 ± 10.37, P < .05) and 58.65% and 57.31% lower in the model group (Nissl bodies: 47.80 ± 4.91 vs. 115.60 ± 11.97, P < .05; Akt-positive cells: 58.10 ± 4.98 vs. 136.10 ± 10.37, P < 0.05), respectively. However, the number of Nissl bodies and Akt-positive cells in the hippocampus of DG group were 74.48% and 62.9% higher compared with the model group, respectively (Nissl bodies: 83.40 ± 7.01 vs. 47.80 ± 4, P < 0.05; Akt-positive cells: 94.70 ± 8.23 vs. 58.10 ± 4.98, P < .05). In addition, compared with the sham group, the number of caspase-3-positive cells, the expression level of p38 mitogen-activated protein kinase (MAPK) and the expression of matrix metallopeptidase 9 (MMP-9) were 2-fold, 34.38%, 64.78% higher in the DG group (caspase-3-positive cells: 78.70 ± 6.52 vs. 27.10 ±3.00, P < .05; p-38MAPK: 0.43 ± 0.15 vs. 0.32 ± 0.10, P < .05; MMP-9: 14.83 ± 1.18 vs. 9.00 ± 2.05, P < .05, respectively), and more than 3-fold, 1-fold and 1-fold higher in model group (caspase-3-positive cells: 121.10 ± 11.04 vs. 27.10 ± 3.00, P < .05; p-38MAPK: 0.70 ± 0.12 vs. 0.32 ± 0.10, P < .05; MMP-9: 19.00 ± 1.90 vs. 9.00 ± 2.05, P < .05), respectively. However, the number of caspase-3-positive cells and the expression levels of p-38MAPK and MMP-9 were 35.01%, 38.57% and 28.12% lower in DG group compared with the model group (caspase-3-positive cells: 78.70 ± 6.52 vs. 121.10 ± 11.04, P < .05; p-38MAPK: 0.43 ± 0.15 vs. 0.70 ± 0.12, P < .05; MMP-9: 14.83 ± 1.18 vs. 19.00 ± 1.90, P < .05). Conclusions Our study showed that diammonium glycyrrhizinate at 20 mg/kg/day had a protective effect on cerebral ischemia-reperfusion injury in rats by promoting formation of Nissl bodies and increasing protein expression of Akt while decreasing that of caspase-3, p38 MAPK and MMP-9, either directly or indirectly, by inhibiting apoptosis and reducing neuroinflammation. All these mechanisms resulted in improved overall neurological function.